Automatic question determination level based on OBE using brute force string matching - Loo Zhang, Bin (2013)
Applying outcome-based education (OBE) in teaching and learning at the tertiary education level has become an important initiative in Malaysia as taken by the government. However, since the concept of OBE is relatively new, some lecturers face difficulty in evaluating the level of question that they produce. Hence this research aim is to develop an automatic question determination level based on OBE using brute force string matching prototype. The focus on this system is to generate a final exam question template with specific fonts and spacing and to evaluate the level of final exam question based upon the teaching and learning taxonomy published by UPM using string matching technique. The major findings that emerged are as follows: a) the suitable string matching technique to be use is brute force string matching due to the nature to the system and development constraints, b) all the outcomes are categorized into two main domains, including the Cognitive and Psychomotor domains. Furthermore, the development process is done using waterfall model software development life cycle. In conclusion, this system is to help user reduce the process and the workload of generating a final exam template.